PENGARUH LATIHAN SIRKUIT TRAINING TERHADAP KEMAMPUAN VO2max ATLET PORPROV TARUNG DERAJAT LOMBOK TIMUR - Jamaludin, Jamaludin (Gelora : Jurnal Pendidikan Olahraga dan Kesehatan IKIP Mataram, 2021)
This study was conducted to determine whether there is influence of circuit training on the ability of VO2max Porprov Tarung Derajat East Lombok Athletes, the purpose of this study was to determine the effect of circuit training on the ability of VO2max Porprov Athlete Tarung Derajat East Lombok. in this study the Porprov athlete Tarung Derajat East Lombok. There are 12 people. The sampling technique is purposive sample. The instrument carried out in this study was running with a distance of 2.4 km. After that, the data was processed with statistics. The hypothesis proposed is that there is the effect of circuit training on the ability of VO2max Porprov Athlete Tarung Derajat, East Lombok. The results of the durability pree-test after calculating produce a t-count of yielding t-count of 0.891 and t-table of 0.697, at the level of alpha (Î±) 0.05 Means tcount > t table. Thus, it can be concluded that there is an effect of circuit training on the ability of VO2max Porprov Athlete Tarung Derajat East Lombok